Project productions with real-life problems in the STEM domain of gifted youths according to their program evaluations. (May 2023) - Özbek, Gülnur; Cho, Seokhee
This study aimed to examine project productions of gifted youths with real-life problems in the STEM domain in the Upper-Lower Groups according to their program evaluations. A mixed research design was used. Education program evaluations of 105 gifted youths, who were attending the Project Production and Management Program at Science and Art Centers in the Republic of Türkiye, were analyzed. It was found that even though they had positive views on the effectiveness of program, there was a significant difference between the lower-27% and upper-27% groups. In the second part, project productions of gifted youths in the Lower-Upper Groups were examined. Even though they were able to produce projects with real-life problems in the STEM domain, differences in favor of the Upper Group were concluded in terms of interdisciplinary connections, complexity of real-life problems, originality of ideas, creative productivity, validation of the solutions, transformation into products, and universality of dissemination.